2000
DOI: 10.1038/75015
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent enteric helminth infection modulates inflammation and gastric immune responses and reduces helicobacter-induced gastric atrophy

Abstract: Helicobacter pylori is causally associated with gastritis and gastric cancer. Some developing countries with a high prevalence of infection have high gastric cancer rates, whereas in others, these rates are low. The progression of helicobacter-induced gastritis and gastric atrophy mediated by type 1 T-helper cells may be modulated by concurrent parasitic infection. Here, in mice with concurrent helminth infection, helicobacter-associated gastric atrophy was reduced considerably despite chronic inflammation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
338
0
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 451 publications
(365 citation statements)
references
References 33 publications
24
338
0
1
Order By: Relevance
“…28,38 In addition, it has been suggested that the Th1 response may also mediate gastritis and gastric cancer. 39 Several studies have shown that T lymphocytes of Stat6-deficient mice fail to differentiate into Th2 cells in response to IL-4 or IL-13. 40,41 RANKL, a member of the TNF cytokine family, is also specifically expressed in Th1-type T lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…28,38 In addition, it has been suggested that the Th1 response may also mediate gastritis and gastric cancer. 39 Several studies have shown that T lymphocytes of Stat6-deficient mice fail to differentiate into Th2 cells in response to IL-4 or IL-13. 40,41 RANKL, a member of the TNF cytokine family, is also specifically expressed in Th1-type T lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic infections favor immunosuppression, the so-called modulated Th2-response, associated with poor parasite-specific reactivity alongside with the strong production of anti-inflammatory cytokines, such as IL-10 and TGF-b [1]. This helminth-induced immunosuppression may spill over to bystander antigens [3], downmodulate reactivity against other pathogens [4] and impair vaccination efficacy [5]. However, such effects can be beneficial by downregulating inflammatory reactions to allergens and inflammatory disorders of the intestinal tract.…”
Section: Introductionmentioning
confidence: 99%
“…Second, mouse strains susceptible to gastric atrophy, such as C57BL/6 mice, mount strong Th1 cell responses after infection with Helicobacter spp. (74), whereas mouse strains resistant to gastric atrophy, such as BALB/c mice, mount Th2 cell responses. Third, deletion of the gene encoding the Th1 cytokine IFN-γ protects mice from gastric atrophy induced by infection with Helicobacter spp., whereas deletion of the gene encoding the Th2 cytokine IL-4 leads to more severe atrophic gastritis (75).…”
Section: Host Factors That Affect the Development Of Gastric Cancer Gmentioning
confidence: 99%